INTEGRASI NILAI-NILAI PENDIDIKAN ISLAM DALAM MENGIMPLEMENTASIKAN SISTEM PERADABAN MELAYU JAMBI “ADAT BASENDI SYARA’, SYARA’ BASENDI KITABULLAH" DI KOTA JAMBI - Alfina islamiyatu khoiriyah; Ahmad Ridwan; Sumirah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background of this research is the importance of maintaining social harmony amidst the challenges of globalization and modernization, which have the potential to shift traditional values and societal morals. The primary focus of this study is the integration of Islamic educational values into the Jambi Malay civilization system based on the principle of "Adat Basendi Syara’, Syara’ Basendi Kitabullah" (ABSSBK). The research aims to identify the Jambi Malay civilization system within the ABSSBK framework, explain the forms of Islamic educational value integration within it, and analyze the supporting and inhibiting factors of this integration process in Jambi City.The methodology employed is a qualitative approach with field research conducted at the Jambi City Malay Customary Institution (Lembaga Adat Melayu - LAM). Data collection techniques included observation, in-depth interviews with customary leaders, and documentation. The data were analyzed using a descriptive qualitative method to provide a comprehensive overview of the phenomenon under study. The results indicate that the integration of Islamic educational values in Jambi Malay civilization is implemented through the alignment of customary practices with Islamic Sharia. Values such as honesty (ṣidq), trustworthiness (amanah), deliberation (shūrā), and justice are practically reflected in marriage ceremonies, customary deliberations, and dispute resolution mechanisms. The role of LAM Jambi City is crucial as the guardian and educator of these values to ensure they remain relevant amidst modernization. Supporting factors for this integration include high religious awareness among the community and support from regional policies. However, the study also identified several obstacles, namely the influence of global lifestyles on the younger generation, uneven understanding of the ABSSBK philosophy within the community, and the lack of reinforcement of customary values in the formal education curriculum. This research concludes that the Jambi Malay civilization system serves as an effective medium for instilling noble character and religious identity as long as the principles of Sharia remain its fundamental basis.